Laki-Laki adalah Pemimpin bagi Perempuan (Kajian Tafsir Tematik Perspektif Mutawalli Al-Sya’rawi dalam Tafsir Al-Sya’rawi) - Amrullah, Najib; SJ, Fadil; Syaifuddin, Helmi (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
This article discusses the meaning of the verse ar-Rijal Qawwamuna 'ala an-Nisa' bima fadhdhalallhu b'adhamuh 'ala ba'dh in surah an-Nisa' verse 34 according to the interpretation of al-Sya'rawi. This article also explains the dialectic of the scholars in understanding the meaning of the verse. This tafsir study includes a thematic interpretation model that discusses one maudhu 'in the al-Qur'an, namely the discussion about men as leaders for women. In this research, obtained through literature review and processed using descriptive-comparative methods. This study aims to provide understanding and reduce tension in the midst of debates that have not yet found a clear point regarding this verse